ChemInform Abstract: Cascade Catalysis — Strategies and Challenges en Route to Preparative Synthetic Biology. Issue 22 (15th May 2015) - Muschiol, Jan; Peters, Christin; Oberleitner, Nikolin; Mihovilovic, Marko D.; Bornscheuer, Uwe T.; Rudroff, Florian
Abstract: Review: 17 refs.